Antioxidant Potential of Phenolic Compounds from Sonneratia caseolaris Mangrove Roots: Isolation, Spectroscopic Analysis, Molecular Docking, Molecular Dynamic, and In-Vitro Studies - Herawati*, Netti; Putri, Suriati Eka; Negara, Satria Putra Jaya; Irfandi, Rizal; Mazaya, Maulida; Rahman, Abd (Universitas Syiah Kuala, 2025)
Free radicals contribute to the onset of various degenerative diseases, highlighting the need for safe and effective antioxidants. Given the potential side effects associated with synthetic antioxidants, Sonneratia caseolaris is considered a promising natural alternative. This study aims to isolate secondary metabolites from the roots of S. caseolaris, evaluate their antioxidant activity, and analyze their molecular interactions. Extraction was conducted using a range of solvents, and antioxidant activity was assessed using the DPPH (2,2-diphenyl-1-picrylhydrazyl) method. The ethyl acetate fraction exhibited the highest antioxidant activity and was subsequently subjected to isolation procedures. From this fraction, a white crystalline compound with a melting point of 251253C was obtained. Spectroscopic analysis identified the compound as 3,4,5-trihydroxybenzoate, a type of phenolic compound. This compound exhibited very strong antioxidant activity, with an IC value of 6.63 g/mL, which is significantly lower than that of ascorbic acid (17.64 g/mL), indicating higher potency. Molecular docking analysis showed that 3,4,5-trihydroxybenzoate formed strong interactions with active residues of cytochrome c peroxidase, particularly Trp51 and Gly112, through hydrogen bonds and hydrophobic interactions. Additionally, molecular dynamics simulations revealed that the compound-enzyme complex exhibited greater structural stability than the control (ascorbic acid), as indicated by lower residue fluctuations in root mean square deviation (RMSD) and root mean square fluctuation (RMSF) analysis analyses. These findings support the potential of Sonneratia caseolaris as a natural source for the development of antioxidant compounds with strong biological activity and favorable molecular interaction profiles